Factors Influencing the Sustainability of Clove Farming in Tikong Village, North Taliabu District - Elfhy Yanti Kamrin; Munawir Muhammad; Ekaria Ekaria (BIOSAINSTEK, 2026)
The sustainability of clove farming is essential for maintaining farmers’ income and preserving agricultural resources. This study aimed to analyze the factors affecting the sustainability of clove farming in Tikong Village, North Taliabu District. The research was conducted from July to August 2025 using a survey method. A census sampling technique was applied, involving 46 clove farmers. The data consisted of primary and secondary sources and were analyzed using multiple linear regression with the assistance of SPSS.The results showed that economic, social, environmental, technological, and government policy factors simultaneously have a significant influence on the sustainability of clove farming. The coefficient of determination (R²) value of 0.406 indicates that 40.6% of the sustainability of clove farming is explained by these five factors, while 59.4% is influenced by other factors outside the research model. Partially, each factor also has a significant positive effect on sustainability. Technology mastery and government policy were found to have the strongest influence among the variables studied. In conclusion, the sustainability of clove farming in Tikong Village is strongly influenced by economic support, farmers’ social conditions, environmental conservation, the application of agricultural technology, and the role of government policies. Therefore, synergy between farmers and the government is necessary to support the development of sustainable clove farming systems.